The interface structure and mechanical properties of Ti/Al dissimilar metals friction stir lap welding - Tang Guangyao; Wang Zhanrui; Ping Zhuoran; Yuan Xuchong; Yu Hui (High Temperature Materials and Processes)
In order to improve the quality of the bonding interface between dissimilar metals, friction stir lap welding was used to weld TA1/6061Al. The effects of multi-pass welding parameters on the mechanical properties, elements distribution, and intermetallic compounds of the lap interface were investigated. The results showed that the fracture locations of the specimens under multi-pass welding and single-pass welding were different. The latter was sheared from the bonding interface, while the former failed near the thermo-mechanically affected zone on the advancing side of the Al side. Moreover, multi-pass welding significantly improved the tensile-shear resistance of the joints. The maximum fracturing load of multi-pass welding reached 7,150 N when adjacent welds interval (L) was 12 mm, which was much higher than single-pass welding 3,861 N. The thermal–mechanical coupling effect of the tool during the welding process resulted in the formation of Ti/Al atomic diffusion layers of different thicknesses and the formation of Ti/Al intermetallic compound (mainly TiAl3) at the bonding interface. Diffusion bonding was the main way for multi-pass welded lap joints to form a reliable connection. The thicknesses of the interfacial diffusion layers at the first weld of multi-pass welding under different L values were approximately the same as that of single-pass welding, in the range of 4–4.4 μm.